Implementation of Restorative Justice Based on Aceh Qanun Number 9 of 2008 Regarding the Settlement of Criminal Acts of Assault in Aceh Besar - Citra Yudha, M. Ryan; Mandasari Saragih, Yasmirah (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The implementation of restorative justice in handling criminal acts of abuse in Aceh Besar based on Aceh Qanun Number 9 of 2008 is an effort to integrate local values with a modern approach to law enforcement. This Qanun provides a legal framework for the Acehnese people to resolve criminal conflicts through customary mechanisms that emphasize reconciliation, restoring relationships between perpetrators and victims, and community involvement in the resolution process. This article explores how restorative justice is applied in cases of abuse in Aceh Besar, focusing on the role of customary institutions in mediation and conflict resolution. Through a qualitative analysis of several cases of abuse, it was found that this approach is not only effective in reducing recidivism rates, but also in strengthening social cohesion in the community. However, the implementation of restorative justice based on this Qanun faces challenges, including a lack of community understanding of customary law procedures and limited support from law enforcement officers. This study concludes that the integration of customary law and restorative justice in Aceh Qanun Number 9 of 2008 has great potential to improve the criminal justice system in Aceh, provided that there is increased socialization and coordination between customary institutions and formal legal institutions.